CFH Y402H polymorphism in Italian patients with age-related macular degeneration, retinitis pigmentosa, and Stargardt disease. (2nd November 2018) - Sodi, Andrea; Passerini, Ilaria; Bacherini, Daniela; Boni, Luca; Palchetti, Simona; Murro, Vittoria; Caporossi, Orsola; Mucciolo, Dario Pasquale; Franco, Fabrizio; Vannozzi, Lorenzo; Torricelli, Francesca; Pelo, Elisabetta; et al.
ABSTRACT: Background : The complement system has been implicated in the pathogenesis of age-related macular degeneration (AMD) and the CFH Y402H polymorphism has been suggested as a major risk factor for AMD. Recent evidences supported the role of inflammation in the pathogenesis of some retinal dystrophies. Aim of this study was to evaluate the prevalence of CFHY402H polymorphism in a group of Italian patients affected by atrophic AMD, Stargardt disease (STGD), or retinitis pigmentosa(RP). Materials and Methods : Our case–control association study included 116 patients with atrophic AMD, 77 with RP, 86 with STGD, and 100 healthy controls. All the patients were evaluated by a standard ophthalmologic examination and OCT. ERG was performed on STGD and RP patients. All the subjects underwent a blood drawing for genetic testing and the CFHY402H polymorphism was genotyped with the TaqMan real-time polymerase chain reaction single nucleotide polymorphism assay. Results : The prevalence of the risk genotype C/C was higher in the AMD group than in controls ( p < 0.001). The risk allele C was more frequent in the AMD group than in controls ( p < 0.001). The prevalence of the risk genotype was higher in the RP patients than in controls ( p < 0.001) and similarly the risk allele C was more frequent in the RP group ( p = 0.008). The CFHY402H genotype distribution was not different between patients with STGD and the controls, for the biallelic ( p = 0.531) and for the monoallelic ( p = 0.318) evaluation. Conclusions : In our series of Italian patients, the CFHY402H genotype is associated with atrophic AMD and RP, but not with STGD. This result may support the hypothesis of a complement system dysregulation in the pathogenesis of AMD and RP